2015
DOI: 10.1111/jnc.13140
|View full text |Cite
|
Sign up to set email alerts
|

Identification of precursor microRNAs within distal axons of sensory neuron

Abstract: A set of specific precursor microRNAs (pre-miRNAs) are reported to localize into neuronal dendrites, where they could be processed locally to control synaptic protein synthesis and plasticity. However, it is not clear whether specific pre-miRNAs are also transported into distal axons to autonomously regulate intra-axonal protein synthesis. Here, we show that a subset of pre-miRNAs, whose mature miRNAs are enriched in axonal compartment of sympathetic neurons, are present in axons of neurons both in vivo and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…Similar to zebrafish, miR-31 expression is ubiquitous in the sea urchin embryo; however, it localizes to punctate structures that do not appear to be nuclear, a pattern that was found typical for only a few miRNAs, such as miR34b, in zebrafish embryos, and for a number of dendritic or axonic miRNAs, such as miR-26a, miR-124a, pre-miR-25 and pre-miR-433, in rats (Kye et al, 2007;Wang et al, 2013;Goldie et al, 2014;Kim et al, 2015). miRNAs or pre-miRNAs that show punctate localization in dendrites or axons are thought to be compartmentalized to perform localized activity-dependent translation (Goldie et al, 2014;Kim et al, 2015). Further study is required to identify the nature of the punctate pattern of miR-31 in the sea urchin embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to zebrafish, miR-31 expression is ubiquitous in the sea urchin embryo; however, it localizes to punctate structures that do not appear to be nuclear, a pattern that was found typical for only a few miRNAs, such as miR34b, in zebrafish embryos, and for a number of dendritic or axonic miRNAs, such as miR-26a, miR-124a, pre-miR-25 and pre-miR-433, in rats (Kye et al, 2007;Wang et al, 2013;Goldie et al, 2014;Kim et al, 2015). miRNAs or pre-miRNAs that show punctate localization in dendrites or axons are thought to be compartmentalized to perform localized activity-dependent translation (Goldie et al, 2014;Kim et al, 2015). Further study is required to identify the nature of the punctate pattern of miR-31 in the sea urchin embryo.…”
Section: Discussionmentioning
confidence: 99%
“…However, several lines of evidence indicate that axons can sprout after injury in adult central nervous system [812]. Recent studies show that distal axons of embryonic cortical neurons contain miRNA machinery proteins, Dicer and argonaut 2 protein (Ago2) and are enriched with miRNAs that can locally regulate axonal growth [1315]. For example, alteration of the miR-17-92 cluster and miR-29c levels in the cultured neurons promote axonal growth by suppressing their target genes that inhibit axonal growth even under the inhibitory environment with chondroitin sulfate proteoglycans [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs localized to the axons play a critical role in axonal function and viability [8]. In addition to the mature miRNAs, it has also been reported that precursor miRNAs (pre-miRNAs) are localized to axons and dendrites [1517]. Consistent with pre-miRNAs being present in axons, components of the RISC complex involved in miRNA processing have also been shown to be present in the axon [1819].…”
Section: Introductionmentioning
confidence: 99%